Multimorbidity and cancer treatment among the older patients in the United States - Tung Thanh Pham; Avonne E. Connor; Anne F. Rositch (PLoS ONE, 2026)
Introduction The number of individuals who are diagnosed with cancer and other comorbidities continues to increase, and the average number of comorbidities among racial/ethnic minority patients is higher than non-Hispanic (N.H.)-white patients. Therefore, we explored the association between race/ethnicity, comorbidities, and cancer treatment among older Americans diagnosed with the four most common cancer types. Methods In this retrospective cohort study, SEER-Medicare linked data were used to identify 692,159 individuals over 65 years old diagnosed with female breast, colorectal, lung, or prostate cancer from 1992–2011. Multimorbidity was defined as having cancer plus two or more comorbidities. Modified Poisson regression models were used to assess the association between comorbidities and race/ethnicity on cancer treatment within 6 months of diagnosis. Results For all cancers, the percentage of patients receiving treatment declined over time and with increasing age, number of comorbidities, and advanced cancer stage. Variability in receipt of treatment by race/ethnicity was observed: 76% for NH-White, 75% for Hispanic, and 68% for NH-Black patients. Concurrently, multimorbidity was increasing over time for all patients. Adjusting for other covariates, patients with multimorbidity were less likely to receive cancer treatment (RR = 0.987–0.947, all p-value<0.001). Moreover, NH-Black (RR = 0.955–0.865, all p-value<0.001) and Hispanic (RR = 0.987–0.951, all p-value<0.001) patients without multimorbidity were less likely to be treated compared to NH-White patients without multimorbidity. Conclusions Our findings suggest that the prevalence of multimorbidity among older patients with cancer has increased and negatively affected cancer treatment among this population. Racial disparities may exist in cancer treatment and seem to be more pronounced in patients without multimorbidity.